2021
DOI: 10.1038/s41467-021-25188-0
|View full text |Cite
|
Sign up to set email alerts
|

Nodal immune flare mimics nodal disease progression following neoadjuvant immune checkpoint inhibitors in non-small cell lung cancer

Abstract: Radiographic imaging is the standard approach for evaluating the disease involvement of lymph nodes in patients with operable NSCLC although the impact of neoadjuvant immune checkpoint inhibitors (ICIs) on lymph nodes has not yet been characterized. Herein, we present an ad hoc analysis of the NEOSTAR trial (NCT03158129) where we observed a phenomenon we refer to as “nodal immune flare” (NIF) in which patients treated with neoadjuvant ICIs demonstrate radiologically abnormal nodes post-therapy that upon pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 45 publications
(54 reference statements)
1
40
0
Order By: Relevance
“…This is supported by a recently published study showing a specific ‘nodal immune flare’ phenomenon in which NSCLC patients demonstrate radiologically abnormal nodes due to a pathological inflammatory response after neoadjuvant ICIs (16%), but not after neoadjuvant chemotherapy (0%). 35 Such temporary inflammatory response can be observed in lymph nodes and be misinterpreted as disease progression. Although no data directly show the frequency of responding lesions being seen in lymph nodes while progressive lesions may be in other viscera, avoiding using lymph nodes as target lesions and exclusion of lymph nodes in response criteria for immunotherapy should be considered, to precisely defined patients with DR or other atypical responses.…”
Section: Pathological Features and Probable Mechanisms Of Immune-rela...mentioning
confidence: 99%
“…This is supported by a recently published study showing a specific ‘nodal immune flare’ phenomenon in which NSCLC patients demonstrate radiologically abnormal nodes due to a pathological inflammatory response after neoadjuvant ICIs (16%), but not after neoadjuvant chemotherapy (0%). 35 Such temporary inflammatory response can be observed in lymph nodes and be misinterpreted as disease progression. Although no data directly show the frequency of responding lesions being seen in lymph nodes while progressive lesions may be in other viscera, avoiding using lymph nodes as target lesions and exclusion of lymph nodes in response criteria for immunotherapy should be considered, to precisely defined patients with DR or other atypical responses.…”
Section: Pathological Features and Probable Mechanisms Of Immune-rela...mentioning
confidence: 99%
“…This was due to immune-cell infiltration into the tumour, rather than tumour growth [ 39 ]. In an ad hoc analysis of the NEOSTAR trial, a “nodal immune flare” (NIF) phenomenon was observed in which patients treated with neoadjuvant ICIs demonstrate radiologically abnormal nodes post-therapy that upon pathological evaluation were devoid of cancer and demonstrated de novo non-caseating granulomas [ 40 ]. This occurred in approximately 16% of patients treated with ICIs.…”
Section: Surgically Resectable Stage III Nsclcmentioning
confidence: 99%
“…The rationale of using immunotherapy as a neoadjuvant treatment lies in the concept that the administration of an ICI while the primary tumor is still in the patient will result in a better systemic anti-tumor immune response. Preclinical in vivo studies in murine models of breast and lung cancer have shown that neoadjuvant immunotherapy works better than immunotherapy in the adjuvant setting, supporting the hypothesis that ICI therapy would be more efficient in driving the anti-tumor T cell response when the tumor mass contains a high antigen burden to be recognized by host T cells [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 95%
“…This phase 3 clinical trial was preceded by several clinical trials that have shown the feasibility and efficacy of several immunotherapeutic approaches for neoadjuvant therapy alone or in combination in patients with resectable NSCLC Stage IB, II, and III. These studies have shown a low toxicity and a high percentage of patients achieving a major pathological response (MPR) and cPR [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%